Microwave processing of oil contaminated drill cuttings - Pereira, Igor S. M. (2013)
Easily accessible oil reserves are currently decreasing, leading to an increase in more complex offshore deep-sea drilling programs, which require increasingly greater depths to be drilled. Such wells are commonly drilled using oil based muds, which leads to the production of drilled rock fragments, drill cuttings, which are contaminated with the base oil present in the mud. It is a legal requirement to reduce oil content to below 1 wt% in order to dispose of these drill cuttings in the North Sea and microwave processing is suggested as a feasible method of achieving the desired oil removal. However, there are currently gaps in our understanding of the mechanisms behind, and variables affecting, the microwave treatment of oil contaminated drill cuttings. The work described in this thesis seeks to address some of these gaps in knowledge.